PERAN PLANETE URGENCE (PU) DALAM RESTORASI EKOSISTEM MANGROVE DI DELTA MAHAKAM 2020-2021 - Algansyah Nandifa Asfia Nur; Muhammad Faisal Aziz (Regionalism Global Journal: Jurnal Hubungan Internasional, 2025)
The Mahakam Delta has suffered severe mangrove ecosystem degradation due to land conversion into aquaculture ponds and mining activities that have caused pollution and environmental decline. This study examines the role of Planete Urgence (PU), a French non-governmental organization (NGO), in restoring the mangrove ecosystem through collaboration with local NGOs. Using a qualitative descriptive method, data were collected through interviews and literature review, then analyzed using the Green Thought Theory and McCormick’s Environmental NGO Strategy Concept. PU plays three main roles; promoting environmental sustainability, social justice, and community participation, while implementing six key environmental NGO strategies. The program has improved restoration effectiveness, achieving a mangrove survival rate of over 80%, increasing aquaculture productivity by 30%, and fostering creative economic initiatives and conservation-based ecotourism. The study concludes that PU, as a non-state actor, contributes significantly to advancing environmental diplomacy and achieving sustainable development at both local and global levels.